Penerapan Metode Permainan Edukatif Terhadap Pembentukan Karakter Peserta Didik di SD IT Rabbani Watampone - Fatmawati, Dewi (JURNAL AL-QAYYIMAH, 2020)
This study examines the implementation of the educational game method of character building students at SD IT Rabbani Watampone. Research includes the type of qualitative research the instrument consists of; Observation guides, interview guidelines and documentation tools. Data processing follows qualitative data procedures namely; Data reduction, data display, and conclusion withdrawal. The results showed that the application of the educative game method in SD IT Rabbani Watampone became a stimulant for the motivation of learners to spirit following the learning process. However, in its application are constraints, including the limited playing facilities and time allocation in the learning process through an insufficient educational method of play. But the school does a preventive step in the among them are the procurement of educational game tools periodically through the policy of school financing, the implementation of teacher training (teaching personnel) in the development and strengthening of learning with educational tools, provide a proportional allocation (including during the hours of school home) to the implementation of educational games and parents already know it because it has done prior coordination and process adaptation and introduction of fast and measurable media. The positive impact of implementing the educational game method for the students ' character is to make the students responsible, independent, honest, appreciate the achievements of others, friendly, fond of reading, environmental care and hard work, discipline and cooperation.